Cambodia - Stads, Gert-Jan; Chanthy, Pol; Nin-Pratt, Alejandro; Omot, Norah; Nguyen, Pham Thi; Makara, Ouk (International Food Policy Research Institute, 2020)
Despite a considerable increase in agricultural research spending in recent years, Cambodia is still grossly underinvesting. At just 0.22 percent in 2017, the country’s agricultural research intensity ratio (that is, spending as a share of AgGDP) is very low.